The labor potential reproduction in depopulation period of 2019–2035 and the compensating role of migration - A. V. Topilin; O. D. Vorob’eva; A. S. Maksimova (Статистика и экономика, 2019)
Purpose of the research. To examine the dynamics of reproduction of labor potential and labor supply in Russia for the period up to 2035, depending on the impact factors of its reproduction: generation change (changes in the proportion of cohort, entering and leaving at the age composition of the labor potential), fertility and mortality rates, migration balance in the individual age cohorts.  Materials and methods. The concept of “replacement of generations” is introduced. The coefficient of replacement of generations is developed and its value for labor potential of Russia for the period up to 2035 is calculated. The influence of factors of natural population movement on the dynamics of labor potential is analyzed. The compensating role of the migration factor in the conditions of labor potential reduction is calculated. Russian regions were grouped according to the following criteria: the direction and intensity of changes in the working-age population in 2020–2035 and the proportion of young people aged 0–15 years.  Results.  – There will be the reduction and aging of labor potential during the second stage of depopulation due to demographic factors.  – The decline in the working-age population in the second wave of depopulation is expected to be smaller than in the first wave.  – In Russia there will be a decrease in the replacement of generations in the contingent of people of the working age.  – The growth of Total Fertility Rate (TFR) in the forecast period should not be expected, because until 2030 a gradual decrease in the number of women of reproductive age is expected.  – The deepest failure in the population of the working age will be in 2020–2025 accounting for 1.7 million people according to the average variant of the forecast.  – In the forecast period, the labor force in the most productive age of 25–39 years will decrease by 10.5 million people, and the employment rate will decrease from 65.5% to 63.5%.  – Regional features of the formation of demand and supply of labor force in Russia cause the allocation of six homogeneous groups of regions.  – In order to compensate for the losses, it is necessary to increase the migration gain in the average version of ROSSTAT forecast by 2–2.5 times.  Conclusion. To meet the needs of the economy in the labor force in the forecast period, it is necessary to solve two interrelated tasks: compensation for the reduction of labor potential and ensuring the quality of labor potential necessary for the introduction of new technologies and digitalization of the economy. The unfavorable situation with the formation of labor resources is exacerbated by regional imbalances in the distribution of labor potential and differences in its quality across the country. In the future, migration is once again the only source of replenishment of labor potential and replacement of generations, despite the risks of quality losses due to the emigration of highly qualified persons and young people. It is necessary to take measures to increase the compensatory role of migration in the next five – six years. At the same time, migration policy measures should be considered in close conjunction with other measures to stimulate fertility and reduce mortality, ensuring a positive impact on the components of the population growth.